Implementation of e-Commerce on ADA Bakery based on Codeigniter Framework: Implementasi e-Commerce pada ADA Bakery berbasis Codeigniter Framework - Rizky Tahara Shita; Lihin Lauw; Fatmasari Tarigan (SYSTEMATICS, 2022)
ADA Bakery is a conventional store, where buyers come physically to buy bread. The promotional media used only use whatsapp and posters displayed in the store, so that product information sold is only limited to the store environment. One of the main points in selling is getting more customers, therefore we need a way so that product information can be marketed more broadly. By utilizing this technology, one of them can be done by marketing it through e-commerce media in order to increase sales significantly. E-commerce development for ADA Bakery is based on Codeigniter Framework, where an open source web application framework and PHP programming language are built dynamically.